Analysing the Effect of Decoupling on Agricultural Production: Evidence from Irish Dairy Farms using the Olley and Pakes Approach - Andrius Kazukauskas; Carol Newman; Fiona Thorne (German Journal of Agricultural Economics (GJAE), 2010)
Recent reform of the Common Agricultural Policy has led to the decoupling of direct payments to farmers from production. This policy change is expected to make farmers' production decisions more market oriented as their subsidy revenue maximization objectives become profit maximizing objectives. In this paper we explore the impact of decoupling on the productivity of Irish dairy farms using a modified version of Olley and Pakes methodology for productivity estimation. We isolate the effect of decoupling on productivity by controlling for other policy changes that have occurred alongside decoupling. We also explore the effect that uncertainties associated with increased price volatility may have had on farmers' decisions in the post-decoupled period.
Keywords: 330; Milchviehhaltung; EU-Agrarpolitik; Agrarproduktion; Irland